Istiwā’ dalam Tafsir Indonesia: Analisis QS. Yūnus [10]: 3 pada Tafsir Hidāyat Al-Qur’ān karya Afifuddin Dimyathi - Rasya' Alfirdaus; M. Imala Bima; Aqila Farah N.; M. Abidtsar Maulana S.; Miladya Laili Sania; Ahmad Musthofa (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2025)
This study addresses a gap concerning the semantics of istiwā’ in Afifuddin Dimyathi’s Tafsir Hidayat al-Qur’ān. Using qualitative, text-based content analysis, it examines the QS Yūnus 10:3 entry in dialogue with QS al-Shūrā 42:11 to show how istiwā’ is framed within iṡbāt, thereby preserving communicability while avoiding takyīf, tasybīh, and ta‘ṭīl. Primary data come from the latest available edition of the tafsīr; secondary materials include classical and modern commentaries and studies on mutasyābihāt. The findings indicate genealogical resonance with Ibn Kathīr’s method of accepting the wording as transmitted and sustained reliance on a Qurʾan-by-Qurʾan framework, supported by sound ḥadīṡ, early reports, linguistic principles, and calibrated ijtihad. The study contributes by clarifying the place of istiwā’ within a local bi al-ma’ṡūr tradition and by proposing pedagogical criteria that prioritize the scriptural text, elucidate it through muḥkam verses, and delegate the “how” in order to safeguard tanzīh.